ANALISIS PEMBANGKIT LISTRIK DENGAN GENERATOR STIRLING - ., Harry Iqbal Al-Fikri (Faculty of Engineering, Universitas Tanjungpura, 2014)
- In this study, using the Stirling Generator TE specification (temperature hot) = 350 C = 623 K, TC (Cold Temperature) = 50 C = 313 K, fluid work = 286 J / (Kg.K), and the angle between the cylinder expansion cylinder compression (dx) = 90 , the piston diameter (D) = 51 m = 0.051 m, length of step / Stroke (S) = 54 mm = 0.054 m, volume expansion (VE) and the compression volume (Vc) = 3.086 x 10 -4 m3, Stirling Speed ??= 750 rpm (assumed), maximum pressure = 325,266.95 Pa, Power = 401.18 Watts at 750 rpm. Based on the analysis of output power depends on the difference in air temperature in the cylinder heat with the air temperature in the cold cylinder, the working fluid is used, and the angle between the cylinder and the cylinder compression expansion. The comparison of work output to the heat input so that the Stirling Generator efficiency scores are good enough to use a power plant.